EFFECT OF AGRIMIN ON FEED CONVERSION, SPECIFIC GROWTH RATE AND PROTEIN EFFICIENCY RATIO OF THE INDIAN MAJOR CARP, LABEO ROHITA (HAM.) - SHARMA, O. P.; RAI, H.O.; KISHAN, RAM (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1997)
The digestibility, feed conversion ratio, specific growth rate and protein efficiency ratio were studied for India major carp, Labeo rohita (Ham) fingerlings fed a traditional diet, i.e. rice bran and oil cake (1:1) containing various doses of a mineral mixture, Agrimin. Best results were obtained with the treatment which had Agrimin at the rate of 3.75 g/kg of feed. The respective values for digestibility, FCR, SGR and PER for 60 days experiment were 88.58%, 59.19 g, 0.405 % and 5.51 g, The effect of Agrimin was found to be highly significant at 1% level and the differences among results of various treatments were also significant as indicated by Critical Difference.